Affecting Factors on Rural Tourism Investment Analyzed through Grounded Theory: The Case of the Villages of Larijan District, Amol, Iran - HESAM, Mehdi; KAZEMI, Mohammad; REZAZADEH, Mohammad (Journal of Environmental Management and Tourism, 2016)
Tourism, just like other service oriented industries worldwide is a great contributor to the economic, social, cultural and political realms of the given country. Tourism, as an industry is a new phenomenon which encompasses capital, human resources, and all socio economical and cultural aspects of the host country by establishing a network. Accordingly, one of the major strategies for having sustainable development in rural sectors is the rural tourism. This factor has created an investment-oriented mentality in this field. By adopting the grounded theory and qualitative paradigm, attempt is made here to identify the affecting elements for the purpose of attracting domestic investors in tourism industry. The data is compiled through in-depth interviews and Focus Group Discussions. The statistical population consists of 216 potential investors in the study area and the sampling follows the snowball effect method resulting in the selection of 40 candidates. A total of at least 35 hrs and 30 min are spent on interviewing the 40 investors in order to obtain the theoretical notion. The most effecting factors in attracting investors are: the capital, interests thereof, regulations, spatial features, structural fundamentals, advertisement, economics, culture, policy makings, institutions and the social elements.
Keywords: rural tourism; investment; grounded theory; qualitative study; Larijan district